Sistem Penghimpunan Dan Penyaluran Dana Masyarakat Pada Bri Unit Manda (Studi Kasus pada Kota Tegineneng Lampung Selatan) - Gatot Hidayat; Shinta Deswati; Goenawan GOENAWAN (Universitas Bandar Lampung (UBL), 2012)
The purpose of the writing of this skripsi is to figure out how to fund from the public and how the distribution of the funds that have been raised by a Bank. This research is expected to add insights and broaden the knowledge within the company, in particular banking institutions that deal with the compilation and distribution. System and management conducted by BRI Unit manda already good because it is done by computerization so quite effectively. However, this system had disadvantages. one of them is the BRI Unit cannot directly determine the financial statements after the occurrence of a transaction. The recording and production of the financial statements is conducted daily, which directly monitored by BRI. The new Unit can know BRI print out financial statements for 1 (day) the next day. From the descriptions above, so it is recommended that the authorized padaBRI Center for BRI units to create their own daily financial reports. So it will be able to know the results of a print out daily transactions on the BRI Unit after working hours. And no need to wait for the next day. It is intended to anticipate when subject happens to financial troubles on a BRI units that must be completed on the same day. The financial statements are needed in decision-making in solving problems. When waiting for results of a print out from the Center the next day, BRI, will delay solving problems that may occur on this day